Upaya Meningkatkan Prestasi Belajar PPKn Materi Pancasila dan Simbolnya Menggunakan Media Pembelajaran Ular Tangga - Dewi Mustika (STAI Muhammadiyah Paciran Lamongan, 2025)
Students did not respond to the material presented by the teacher, as a result, after the presentation of the learning material was completed and an evaluation was carried out, it turned out that out of 28 students consisting of 15 females and 13 males in class V of SDIT Nurul Akbar Klaten Utara, only 10 students had mastered the material. It was proven that out of 28 students in class V of SDIT Nurul Akbar Klaten Utara, they got an average class score of 60 and only 10 students got the same score or above the KKM 75, while the other 18 students got a score of less than 75. The purpose of this study was to describe the application of learning media using snakes and ladders learning media in improving PPKN learning achievement, Pancasila material, and its symbols for class V students in semester 1 of SDIT Nurul Akbar Klaten Utara in the 2022/2023 Academic Year. This research is an experimental research with Cycle 1 and Cycle 2 research designs. The subjects of this research were fifth-grade students in semester 1 of SDIT Nurul Akbar Klaten Utara in the 2022/2023 Academic Year. This research method uses qualitative, data collection techniques using tests, observations, and documentation with comparative data analysis techniques. The results of the data analysis were calculated from the beginning before the research, Cycle 1 research activities, and Cycle 2 research activities. Thus, it can be concluded that the snakes and ladders game can improve the learning achievement of fifth-grade students in semester 1 of SDIT Nurul Akbar Klaten Utara in the 2022/2023 Academic Year in PPKN on the Pancasila and its symbols material.